PENGEMBANGAN SENTRA KERUPUK BAWANG BUM DESA KARANGCANGKRING BERBASIS KELOMPOK PKK DI KABUPATEN GRESIK - Dwiyana Anela Kurniasari; Siti Alimah; Achmad Zaki Fadhil (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
This Community Service (PKM) activity aims to increase the production capacity and quality of the onion cracker business managed by the Family Welfare Movement (PKK) Group in Karangcangkring Village, Dukun District, Gresik Regency. The partners' main problems included inconsistent product quality, as well as limitations in packaging and marketing. The solutions provided included technical training, business management assistance, and digital marketing strategies. The activity results showed that new packaging with a local brand identity successfully increased the product's appeal and selling value. In addition, the use of social media in promotions was able to increase sales by up to 30%. This program successfully encouraged the independence of the PKK group's business and strengthened the village's potential as a Village-Owned Enterprise (BUM Desa)-based onion cracker center. Needs-based interventions and solutions have proven effective in accelerating the transformation of micro-enterprises into more productive and competitive businesses.